Thalictrum changii (Ranunculaceae), a new species from southern Xizang (Tibet), China - Zeng, You-Pai; Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Thalictrum changii (Ranunculaceae), a new species from southern Xizang (Tibet), China, is illustrated and described. Morphologically, T. changii is most closely similar to T. yunnanense in habit and in having 2–3-ternate leaves, paniculate-corymbiform inflorescence, clavate filaments, sessile, fusiform achenes, and glandular-pubescent leaves, inflorescence rachis, pedicels and achenes, but differs by having subcoriaceous (vs. papery) leaflets, narrowly elliptic (vs. suborbicular), longer (ca. 5 mm vs. ca. 3.5 mm) and persistent (vs. caducous) sepals, and longer (ca. 3 mm vs. ca. 1.5 mm) carpels with longer (ca. 1.5 mm vs. ca. 0.5 mm) styles. The confusion in the geographical distribution of T. yunnanense and its closely allied species T. scabrifolium is clarified. Morphological distinction between the two varieties of T. yunnanense, namely var. yunnanense and var. austroyunnanense, is discussed. An identification key to T. changii and its closely allied taxa is also provided.